2021
DOI: 10.1038/s41598-020-80574-w
|View full text |Cite
|
Sign up to set email alerts
|

Tropical rhodolith beds are a major and belittled reef fish habitat

Abstract: Understanding habitat-level variation in community structure provides an informed basis for natural resources’ management. Reef fishes are a major component of tropical marine biodiversity, but their abundance and distribution are poorly assessed beyond conventional SCUBA diving depths. Based on a baited-video survey of fish assemblages in Southwestern Atlantic’s most biodiverse region we show that species composition responded mainly to the two major hard-bottom megahabitats (reefs and rhodolith beds) and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…coral, sea urchins, Doropoulos et al, 2012; Gómez‐Lemos et al, 2018; Rahmani & Ueharai, 2001; Steller & Cáceres‐Martínez, 2009). Considering adverse effects related to the interaction with other stressors, like coastal pollution (Schubert et al, 2019), predatory fishery (Fragkopoulou et al, 2021) and the importance of their ecosystems to socio‐environmental and economic well‐being (Moura et al, 2021), besides reducing CO 2 emissions, further effort should look to improve ocean health as a whole (Laffoley et al, 2020), fostering the creation of no‐take marine protected areas with focus on these reef builders to enhance their resilience and survival (Sissini et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…coral, sea urchins, Doropoulos et al, 2012; Gómez‐Lemos et al, 2018; Rahmani & Ueharai, 2001; Steller & Cáceres‐Martínez, 2009). Considering adverse effects related to the interaction with other stressors, like coastal pollution (Schubert et al, 2019), predatory fishery (Fragkopoulou et al, 2021) and the importance of their ecosystems to socio‐environmental and economic well‐being (Moura et al, 2021), besides reducing CO 2 emissions, further effort should look to improve ocean health as a whole (Laffoley et al, 2020), fostering the creation of no‐take marine protected areas with focus on these reef builders to enhance their resilience and survival (Sissini et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent tagging experiments showed that adults can perform tens of kilometre displacements during their life cycle, which confirms that the species is less sedentary than previously claimed (Devries, 2006; Haimovici et al ., 2020). When different biotopes were analysed ( i.e ., the presence of the red porgy in different topographic environments), most individuals were detected in rhodolith beds, indicating that these habitats are important foraging areas for the red porgy (Abrecht et al ., 2021; Holz et al ., 2020; Moura et al ., 2021), and predator/prey interactions may play a crucial role in the maintenance of these megahabitats (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding considering the density of nodules of rhodoliths pointed to the strong affinity of the red porgy with rhodolith beds. Recent studies comparing the Brazilian rhodolith megahabitat with reef environments showed outstanding similarities in terms of diversity and productivity (Moura et al ., 2021). Considering the fast growth and long life of such an active carnivore mesoconsumer, subadults and adults of the red porgy should demand a diverse and high‐productivity environment to thrive (Anderson et al ., 2021;Carvalho et al ., 2020; Moura et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations